2015
DOI: 10.3357/amhp.3428.2015
|View full text |Cite
|
Sign up to set email alerts
|

Prospective Memory Failures in Aviation: Effects of Cue Salience, Workload, and Individual Differences

Abstract: Our findings suggest that technologies designed to signal intended future tasks should target those tasks with inherently low-salience memory cues. In addition, increasing the salience of memory cues is most likely to benefit pilots with lower levels of cognitive health in high-workload conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
11
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 0 publications
3
11
0
1
Order By: Relevance
“…For example, research on radar signal detection found that 3D immersion allowed for multidimensional information to be analyzed better, when compared to 2D signals, because the information is presented in a way that is cohesive rather than presented as separate entities (Cantu et al, 2019). This study demonstrates the increased interest in utilizing VR superiority and technology to enhance visual tasks, although the task is not relevant to a typical general aviation task, the results do support that there may be some benefit in utilizing a 3D interface in order to manipulate cue presentation, that has previously been demonstrated (Dismukes 2010;Einstein & McDaniel 2004, Van Benthem, 2015 as a vital component in investigating how cue distinction and display may impact its saliency power.…”
Section: Virtual Reality and Prospective Memorysupporting
confidence: 63%
See 3 more Smart Citations
“…For example, research on radar signal detection found that 3D immersion allowed for multidimensional information to be analyzed better, when compared to 2D signals, because the information is presented in a way that is cohesive rather than presented as separate entities (Cantu et al, 2019). This study demonstrates the increased interest in utilizing VR superiority and technology to enhance visual tasks, although the task is not relevant to a typical general aviation task, the results do support that there may be some benefit in utilizing a 3D interface in order to manipulate cue presentation, that has previously been demonstrated (Dismukes 2010;Einstein & McDaniel 2004, Van Benthem, 2015 as a vital component in investigating how cue distinction and display may impact its saliency power.…”
Section: Virtual Reality and Prospective Memorysupporting
confidence: 63%
“…The first possible explanation is that the VR environment may enhance perceptual triggers, and participants in a VR environment may free up mental resources in monitoring the environment, and therefore have greater mental resources to focus on time-keeping. This explanation is supported through previous work that demonstrates that workload may impact situational awareness and participants in high workload conditions, have been shown to have worse prospective memory performance (Van Benthem, 2015).…”
Section: Vr Superioritysupporting
confidence: 59%
See 2 more Smart Citations
“…High mental workload can cause significant performance decrements and breakdowns in attention allocation (Rouse et al, 1993). Preventing problems related to high workload is critical in complex, safety-sensitive domains, such as aviation, process control, driving, and medicine (e.g., Dixon et al, 2005, Van Benthem et al, 2015), where delays and errors due to high workload can have life-threatening consequences. The 1978 United Airlines DC-8 airplane crash in Portland, OR, for example, was linked to pilots’ high workload as they were trying to address issues with the landing gear (National Transportation Safety Board, 1978).…”
Section: Introductionmentioning
confidence: 99%